Diversity of Morphological’s fruit of Asam Gelugur (Garcinia atroviridis Griff. ex T. Anders) in Asahan Regency, Batubara Regency and Serdang Berdagai Regency in North Sumatera - santa lidwina ginting; Eva Sartini Bayu; Lollie Agustina P.Putri (Universitas Sumatera Utara, 2018)
This reserach aimed to identify the morphological chracteristics and phylogenetic relationship of G. atroviridis and a conservation material in three districts of North Sumatra The research was conducted at Asahan, Batubara and Serdang Berdagai district from Februari to mei 2017 by survey method. G. atroviridis samples founded in three districs were identified and characterzed based on International Plant Genetic Resources Institute (IPGRI) standard. Sampling technique using accidental sampling. Parameters observed were fruit shape, number of fruit segments, fruit diameters, fruit weight, fruit size, fruit skin thickness, mature fruit colour. The result showed that there were 18 accession of G. atroviridis found in three districts. Morphologycal characteristic of G. atroviridis was fruit shape (round, flattened, ovoid,). In fruit morphology showed that the 18 individuals analyzed were divided into 4 groups on a distance scale of 0,796 with a similarity rate of about 79-85.